Analisis Positioning Gerai Minimarket Berdasarkan Persepsi Konsumen di Kota Bandung (Studi pada Alfamart, Circle K, Indomaret, SB Mart, dan Yomart) - Artarika Permatasari (Fakultas Ekonomi Universitas Garut, 2018)
The change in people's lifestyle that demands convenience in fulfilling their needs affects the phenomenon of minimarket business growth. Currently in Bandung, the competition for minimarkets is getting tighter, including among Alfamart, Circle K, Indomaret, SBMart, and Yomart who continue to compete to provide the best service to consumers. The purpose of this study was to determine the positioning of the five minimarket outlets in Bandung, namely Alfamart, Circle-K, Indomaret, SB Mart, and Yomart based on consumer perceptions in the city of Bandung. This consumer perception is measured by six retail mix attributes, including customer service, location, store layout and design, merchandise assessment, communication mix, and pricing. This research uses quantitative methods with descriptive types. The data collection method was carried out by distributing questionnaires online to 390 respondents in the city of Bandung. The data analysis technique in this study is Multidimensional Scaling. The results of the study indicate that Indomaret occupies the first position that excels in the attributes of customer service, location, merchandise assortment, communication mix, and pricing. Alfamart occupies the second position that excels in the store layout and design attributes. Next, Yomart is in third position, Circle K is in fourth position, and SB Mart is in fifth. Suggestions are given, Indomaret and Alfamart must continue to maintain excellence in the attributes that have been obtained so that they still have a good perception in the minds of consumers.